2020
DOI: 10.1186/s12884-020-02948-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of quitting water pipe during pregnancy on anthropometric measurements at birth: a population-based prospective cohort study in the south of Iran

Abstract: Background: Evidence regarding health effects of tobacco cessation during pregnancy is mainly restricted to cigarette while water pipe is the preferred method of tobacco smoking among women in the Middle-East. The present study aimed to assess the effects of cessation of water pipe during pregnancy on birth anthropometric measures in the south of Iran. Methods: Data on 1120 singleton pregnancies (response rate = 93.4%) from a population-based prospective cohort study in suburban communities in Bandar Abbas cit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…The water-pipe has been found to contain the same addictive drug, nicotine that causes dependency in cigarettes (Jukema et al, 2014). Therefore, the water-pipe has similar harmful consequences for both the mother and the fetus (Nematollahi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The water-pipe has been found to contain the same addictive drug, nicotine that causes dependency in cigarettes (Jukema et al, 2014). Therefore, the water-pipe has similar harmful consequences for both the mother and the fetus (Nematollahi et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, women who smoked hookah were less likely than cigarette smokers to change their smoking habits when they became pregnant. A recent prospective cohort study in Iran found that quitting hookah during pregnancy had positive effects on infant growth, especially birth weight [ 42 ]. Targeting hookah smokers to encourage smoking cessation or reduction may have a vital impact on birth outcomes [ 10 , 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%